STUDI KEPUASAN KERJA KARYAWAN DENGAN GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN KARAKTERISTIK PEKERJAAN SEBAGAI VARIABLE BEBAS DI PT SUMBER BINTANG REZEKI KABUPATEN SEMARANG - Singkiran Duha; Andhi Supriyadi (LPSDI Bina Patria, 2022)
Job satisfaction is defined as how well an employee views his or her job. This can be measured by comparing the amount of compensation they receive to the amount of work they do. Finding out how leadership style, work environment, and job characteristics influence job satisfaction is the goal of this research. This research involved 90 employees of PT Sumber Bintang Rezeki, Semarang Regency. The results of multiple regression tests show that factors such as leadership style, work environment, and job characteristics influence job satisfaction. The advice given to PT Sumber Bintang Rezeki, Semarang Regency, is that the leadership should show support for improving employee work abilities by providing care and maintenance of the environment and routines from the agency, namely replacing dim lights, providing lighting, giving employees freedom to carry out tasks according to their way of working or experience. owned as long as it still complies with procedures and authority.